Trends in anti-HER2 drugs consumption and influencing factors - Liu, Jie; Zhang, Xiaolei; Wang, Biao; Dai, Huizhen; Dou, Dahai; Fang, Wentong (Frontiers in Public Health, 2022)
Background: Human epidermal growth factor receptor 2 (HER2) inhibitors have been approved to treat various cancers with HER2 amplification. The Chinese government has made great efforts to improve the availability and affordability of these drugs. This study aimed to analyze the trends in anti-HER2 drug consumptions in Nanjing from 2012 to 2021, and explore influencing factors. Methods: Data about use of anti-HER2 drugs in 2012-2021 were extracted from Jiangsu Medicine Information Institute. Six types of anti-HER2 drugs were included. Drug consumption was expressed as defined daily doses (DDDs) and expenditure. Time series analysis was adopted to find trends in consumption, while interrupted time series was used in analyzing the impact of policy on consumption. The correlation between DDDs and defined daily cost (DDC) was analyzed by Pearson's correlation test. Results: The DDC, DDDs, and expenditure of anti-HER2 drugs changed little from 2012 to 2016. The DDC decreased intermittently, while the DDDs and expenditure of these drugs grew continuously from 2017 to 2021. The anti-HER2 monoclonal antibodies contributed to the majority of total consumption in 2012 to 2019. The DDDs of anti-HER2 tyrosine kinase inhibitors surpassed the DDDs of monoclonal antibodies in 2020 to 2021 (Fig 2A). Trastuzumab was the predominantly prescribed drug in 2012 to 2019, but the DDDs of pyrotinib surpassed the DDDs of trastuzumab in 2020 to 2021. The ln value of DDC or self-paid DDC of trastuzumab was negatively correlated with the ln value of its DDDs. The national health insurance coverage (NHIC) and national drug price negotiation policy about anti-HER2 drugs were initiated in 2017. Low-price generics and biosimilar of trastuzumab came into the market in 2020 and 2021, separately. Interrupted time series analysis showed that the DDDs increased significantly after the implementation of NHIC, price negotiation or generic drug replacement. Conclusion: The consumption of anti-HER2 drugs has significantly increased and their DDC has decreased after the implementation of NHIC, price negotiation, or low-price generic drug replacement since 2017. Further efforts are needed to translate the high consumption into clinical benefits.